Parthanatos and its associated components: Promising therapeutic targets for cancer - Zhou, Yunxiang; Liu, Lihong; Tao, Sifeng; Yao, Yihan; Wang, Yali; Wei, Qichun; Shao, Anwen; Deng, Yongchuan (Pharmacological research, 2021)
[Display omitted] Parthanatos is a PARP1-dependent, caspase-independent, cell-death pathway that is distinct from apoptosis, necrosis, or other known forms of cell death. Parthanatos is a multistep pathway that plays a pivotal role in tumorigenesis. There are many molecules in the parthanatos cascade that can be exploited to create therapeutic interventions for cancer management, including PARP1, PARG, ARH3, AIF, and MIF. These critical molecules are involved in tumor cell proliferation, progression, invasion, and metastasis. Therefore, these molecular signals in the parthanatos cascade represent promising therapeutic targets for cancer therapy. In addition, intimate interactions occur between parthanatos and other forms of cancer cell death, such as apoptosis and autophagy. Thus, co-targeting a combination of parthanatos and other death pathways may further provide a new avenue for cancer precision treatment. In this review, we elaborate on the signaling pathways of canonical parthanatos and briefly introduce the non-canonical parthanatos. We also shed light on the role parthanatos and its associated components play in tumorigenesis, particularly with respect to the aforementioned five molecules, and discuss the promise targeted therapy of parthanatos and its associated components holds for cancer therapy.